2012
DOI: 10.1177/1721727x120100s220
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy (Association Diode Laser/Hydrogen Peroxide): Evaluation of Bactericidal Effects on Periodontopathy Bacteria: An in Vitro Study

Abstract: The main cause for the development of periodontitis is the accumulation of subgingival microbial deposits organized tightly to the porous surface of the tooth cementuni. The growth of the microbial populations and the immunological reaction of the host organism are responsible for the destruction of periodontal ligament apparatus. The primary goal in the treatment of periodontitis is the complete removal of subgingival bacterial deposits. The large amount of evidence establishing a microbial etiology for perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…A comparative study on the effects of laser alone and combined with H 2 O 2 showed these results [ 31 34 ]: Laser used alone produces poor results in the elimination of bacterial species involved in periodontal disease. H 2 O 2 used alone produces little effects in microorganisms elimination.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study on the effects of laser alone and combined with H 2 O 2 showed these results [ 31 34 ]: Laser used alone produces poor results in the elimination of bacterial species involved in periodontal disease. H 2 O 2 used alone produces little effects in microorganisms elimination.…”
Section: Discussionmentioning
confidence: 99%
“…The singlet oxygen is an oxygen free radical that determines bacterial cell death. In many of the studies, the results showed a decrease in total bacterial count (7,8,14,16,(25)(26)(27)(28)(29). The great majority of bacteria investigated were of Gram-negative and were affected by aPDT (7,8,16).…”
Section: Discussionmentioning
confidence: 99%
“…If the wavelength used is absorbed in the chromophore used, laser ray cannot penetrate more in deeper, and if the power density is too low (usually PDT protocols use LLLT (low level laser therapy) energy, in order to avoid any thermal damage), the decontaminating effects are not enough. Recently has been proposed that a combination between high power and high frequency of diode laser 980 nm (using really high peak power combined with a low average power, in order to reduce thermal effects) and hydrogen peroxide 10 volume 3%, or modified hydrogen peroxide 10 volumes 3% [16][17][18][19][20][21][22][23]. This treatment modality was named "photodynamic therapy without dye" (OHLLT; oxygen high level laser therapy) in the protocol proposed by Gerard Rey in 1999 [24].…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study on the effects of laser alone and combined with H 2 O 2 10 vol. 3% showed these results [21][22][23]: (1) laser used alone produces poor results in the elimination of bacterial species involved in periodontal disease, (2) H 2 O 2 used alone produces little effects in micro-organism elimination, and (3) laser combined with hydrogen peroxide shows an antibacterial action that is much more effective on most of the microorganisms involved in periodontal disease. Laser energy activates the modified H 2 O 2 solution, releasing free radicals and singlet oxygen that has antibacterial activity on Gram-positive and Gram-negative periodontal pathogens.…”
Section: Introductionmentioning
confidence: 99%